Serial assessment of spot urine sodium predicts effectiveness of decongestion and outcome in patients with acute heart failure. (17th February 2019) - Biegus, Jan; Zymliński, Robert; Sokolski, Mateusz; Todd, John; Cotter, Gad; Metra, Marco; Jankowska, Ewa A.; Banasiak, Waldemar; Ponikowski, Piotr
Abstract : Aims: The clinical significance of the measurement of urine sodium concentration (UNa + ) in response to loop diuretic administration in patients with acute heart failure (AHF) is still unsettled. We studied the association of serial measurements of spot UNa + during the first 48 h of AHF treatment with the indices of decongestion, renal function, and prognosis. Methods and results: We enrolled 111 AHF patients, all of whom received intravenous furosemide on admission. The mean spot UNa + significantly increased in the 6 h sample ( P < 0.05 vs. baseline) and returned to baseline values in the 24 and 48 h samples. Based on the increase or decrease/no change of UNa + in the 6 and 48 h samples vs. baseline, patients were divided into two groups at each time point, respectively. Patients did not differ in baseline clinical and laboratory characteristics. Patients with a decrease/no change of UNa + in the 6 and 48 h samples had a lower weight loss during hospitalization. Patients with a decrease/no change of UNa + in the 48 h sample had a poorer diuretic response and a significant increase in the urinary levels of the tubular biomarkers: kidney injury molecule‐1 and neutrophil gelatinase‐associated lipocalin. Low UNa + and decrease/no change in UNa + in the 6 and 48 h samples were independent predictors of higher risk of all‐cause mortality during 1‐year follow‐up (all P < 0.05). Conclusion: In AHF, low spot UNa+ and lack to increase UNa + in response to intravenous diuretics are associated with poor diuretic response, markers of tubular injury and high risk of 1‐year mortality.